2015
DOI: 10.1097/md.0000000000001321
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Reverse Seroconversion of Hepatitis B Virus Surface Antigen in Rituximab-Treated Non-Hodgkin Lymphoma Patients

Abstract: Rituximab causes hepatitis B virus (HBV) reactivation in HBV surface antigen (HBsAg)-seronegative patients with CD20-positive B-cell non-Hodgkin lymphoma (CD20+ NHL), especially for those seropositive to the antibody of core antigen (anti-HBc). Clinical hepatitis usually develops after reverse seroconversion of HBsAg (HBV-RS), indicated by the reappearance of HBsAg in serum. Because of the relatively high prevalence of anti-HBc seropositivity in unvaccinated HBsAg-seronegative adults in an HBV hyperendemic are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…The occurrence of late‐onset rHBV supports other previous studies showing that RTX therapy for more than six cycles increased the risk of rHBV with HBsAg seroreversion, and a higher cumulative dose of RTX was associated with increased risk of infection . In addition, the incidence rate (8.7%) of rHBV in our HBsAg‐negative patients is similar to the results (9.1%) of a recent study in Taiwan, although different from another study indicating that rHBV was rare in those with resolved HBV infection . This discrepancy might be related to the differences in characteristics of the enrolled patients and the duration of follow‐up period.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The occurrence of late‐onset rHBV supports other previous studies showing that RTX therapy for more than six cycles increased the risk of rHBV with HBsAg seroreversion, and a higher cumulative dose of RTX was associated with increased risk of infection . In addition, the incidence rate (8.7%) of rHBV in our HBsAg‐negative patients is similar to the results (9.1%) of a recent study in Taiwan, although different from another study indicating that rHBV was rare in those with resolved HBV infection . This discrepancy might be related to the differences in characteristics of the enrolled patients and the duration of follow‐up period.…”
Section: Discussionsupporting
confidence: 87%
“…Rituximab (RTX), a monoclonal antibody directed against B‐cell marker CD20, is effective for treating B‐cell lymphoma and RA patients with inadequate response to anti‐tumor necrosis factor (TNF)‐α therapy . Although a previous study demonstrated no rHBV in RTX‐treated rheumatic patients with resolved HBV infection, rHBV has recently been recognized as a complication characterized by a seroreversion of HBsAg in HBsAg‐negative patients receiving RTX therapy . Despite these findings, there are limited data or even conflicting results on rHBV in RTX‐treated patients .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Hepatitis B virus (HBV) reactivation has been noted in hepatitis B virus surface antigen (HBsAg)-seronegative patients with CD20 + NHL, and at 10% risk of reverse seroconversion of hepatitis B virus surface antigen (HBV-RS). 3 7 Clinically, hepatitis flares are frequently associated with the reappearance of HBsAg (i.e., HBV-RS). 5 Among the risk factors for HBV-RS in HBsAg-seronegative patients with CD20 + NHL, HBV serological status prior to rituximab therapy, including antibody to hepatitis B virus core antigen (anti-HBc) seropositivity and antibody to hepatitis B virus surface antigen (anti-HBs) seronegativity, has been shown to be associated with a significantly increased risk in some reports.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 8 A higher number of cycles of rituximab therapy has also been highlighted as a risk factor. 6 , 7 However, the anti-HBc and anti-HBs seropositivity rate is relatively high in unvaccinated HBsAg-seronegative adults in HBV-hyperendemic areas, 3 , 4 , 6 9 for example, at least 70% in Taiwan, 4 7 , 9 which was the 1st country to initiate universal HBV vaccination, in 1984. 10 Therefore, it is necessary to investigate whether human genetic factors are related to rituximab-associated HBV reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…While the precise mechanism within the host immune response is largely unknown, recent studies suggest that T-cells may not be the major players in the natural history of chronic HBV infection [5]. Importantly, since therapies targeted against CD20 can result in HBV reactivation even after HBsAg loss, this suggests that B-lymphocytes and plasma cells likely play a role in immunity against HBV infection [6]. In patients undergoing autologous stem cell transplant (ASCT), host immunity is presumably restored immediately after chemoablation of cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%